Magnetic resonance imaging in terms of observation of patients after transanal resections of rectal tumors - S. A. Myalina; T. P. Berezovskaya; A. A. Nevolskikh; V. A. Avdeenko; S. A. Ivanov; A. D. Kaprin (Исследования и практика в медицине, 2022)
Purpose of the study. Was to study the results of magnetic resonance imaging (MRI) of the patients with malignant neoplasms (MN) of the rectum after transanal full‑layer resection of the tumor.Materials and methods. MRI images of the pelvis of 25 patients with rectal cancer after organ–preserving surgical treatment in the volume of full‑layer excision of the tumor for the period from 2015 to 2020 of the MRI department of the A. Tsyb Medical Radiological Research Centre, the Branch of the National Medical Research Radiological Centre of the Ministry of Health of the Russian Federation; 13 patients received additional treatment in the volume of chemoradiotherapy and brachytherapy; 13 patients underwent dynamic studies to assess the process after treatment.The MRI picture was evaluated by T2‑WI in three planes and DWI with an ADC map in the pelvic region and aimed at the excision zone of the tumor.Indications for MRI were the exclusion of continued tumor growth in the surgical intervention area and clinical manifestations of suture failure in the tumor excision area.Results. All patients were divided into two groups: 11 patients with a normal course of the postoperative period where visualized a zone of scar changes in the area of surgical intervention with a low intensity signal in the T2‑WI mode, without signs of true diffusion restriction, hyper‑ and the average intensity of the signal and 14 patients with identified deviations from the normal picture: of these 10 patients with a relapse after surgical treatment, who had additional formations with signs of pathological MR signal, true diffusion restriction, which were regarded as recurrent formations in the tumor excision zone, as well as 4 patients in the tumor excision zone, a defect in the rectal wall was visualized against the background of a low intensity signal from the zone of fibrous changes, with the formation of liquid leaks, indicating the insolvency of the seams.Conclusion. The method of MRI can be recommended as the method of choice for assessing the pelvic region after transanal endoscopic microsurgery (TEM), which allows for high accuracy to exclude continued tumor growth; to assess the pelvic region for the presence of distant metastases; to determine the defect of the walls in the excision zone of tumors. MRI provides safe dynamic control.